Pro JSF and HTML5 Building Rich Internet Components - Saleh, Hazem; Christensen, Allan Lykke; Wadia, Zubin; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Pro JSF and HTML5 shows you how to leverage the full potential of JavaServer Faces (JSF) and HTML5. This book is for Java developers who aspire to build sophisticated, enterprise-grade web experiences with HTML5-enabled JSF. Written by JSF experts and verified by established community figures, this book will serve as your primary resource, helping you build or integrate well-designed HTML5-enabled JSF components into your rich internet applications. Pro JSF and HTML5 starts by giving you a firm grounding in the design principles of component-based frameworks and the basics of JSF. It then details recent advancements in JSF 2.2 that make it friendlier, faster, and more productive than ever before. And it covers HTML5-enabled components, integration with JEE7 standards, 3rd party component libraries, security, and performance. The book concludes with a real-world application that puts everything you learned into practice. In this book you$1 (Bll learn Foundational JSF topics such as the component life cycle, framework architecture, managed beans and CDI, expression language, conversion and validation, JSF events and view parameters. Leveraging new features in JSF 2.2 such as Faces Flow, Resource Library Contracts, and Ajax file uploading. Developing Advanced HTML5 enabled components in JSF 2.2. Creating JSF 2.2 applications that utilize Java EE 7 technologies (CDI, JPA 2.1 and EJB 3.2) for bean management, transaction management and persistence. Building advanced real-world JSF applications with considerations for security, performance, and usability. If you$1 (Bre a Java developer interested in the world of component-based frameworks, Pro JSF and HTML5 is for you.s
Keywords: Computer science; Computer Science; Computer Science, general